Robust Route to Unimolecular Core–Shell and Hollow Polymer Nanoparticles - Feng, Chaowei; Pang, Xinchang; He, Yanjie; Li, Bo; Lin, Zhiqun (Chemistry of materials, 2014)
Unimolecular core–shell and hollow polymer nanoparticles with well-defined dimensions were crafted using spherical core–shell star-like diblock copolymers as templates. Monodisperse and structurally stable star-like diblock copolymers composed of inner degradable core blocks and outer photo-cross-linkable shell blocks were synthesized via a combination of two living polymerization techniques, namely, coordination–insertion ring opening polymerization (ROP) followed by reversible addition–fragmentation chain-transfer polymerization (RAFT). Subsequently, uniform unimolecular core–shell nanoparticles were successfully produced by photo-cross-linking the shell blocks of star-like diblock copolymers. The core diameter and shell thickness of nanoparticles are determined by molecular weights of inner core block and outer shell block, respectively, thereby rendering nanoparticles with tunable structural characteristics. The cross-linking density of nanoparticles can be readily controlled by varying the exposure time of star-like diblock copolymer templates to UV illumination. The selective degradation of inner core blocks yielded hollow polymer nanoparticles which retained structural integrity. The dye encapsulation and release studies revealed that unimolecular core–shell nanoparticles may be exploited as a new class of nanocarriers and promising drug nanovehicles.